On the origin of rhythmic contractile activity of the esophagus in early achalasia, a clinical case study - Chen, Ji-Hong; Wang, Xuan-Yu; Liu, Louis W.; Yu, Wenzhen; Yu, Yuanjie; Zhao, Liang; Huizinga, Jan D. (Frontiers in Neuroscience, 2013)
A patient with early achalasia presented spontaneous strong rhythmic non-propulsive contractions at 7/min, independent of swallows. Our aim was to evaluate characteristics of the rhythmic contractions, provide data on the structure of pacemaker cells in the esophagus and discuss a potential role for interstitial cells of Cajal (ICC) in the origin of rhythmicity. We hypothesize that intramuscular ICC (ICC-IM) are the primary pacemaker cells. The frequency but not the amplitude of the rhythmic contractions was inhibited by the phosphodiesterase inhibitor drotaverine consistent with cAMP inhibiting pacemaker currents in ICC-IM. The frequency increased by wet swallows but not dry swallows, consistent with stretch causing increase in slow wave frequency in ICC-IM. New studies on archival material showed that ICC-IM were present throughout the human esophageal musculature and were not diminished in early achalasia. Although ICC-IM exhibited a low density, they were connected to PDGFRα-positive fibroblast-like cells with whom they formed a dense gap junction coupled network. Nitrergic innervation of ICC was strongly diminished in early achalasia because of the loss of nitrergic nerves. It therefore appears possibly that ICC-IM function as pacemaker cells in the esophagus and that the network of ICC and PDGFRα-positive cells allows for coupling and propagation of the pacemaker activity. Loss of nitrergic innervation to ICC in achalasia may render them more excitable such that its pacemaker activity is more easily expressed. Loss of propagation in achalasia may be due to loss of contraction-induced aboral nitrergic inhibition.